Importance of the use of coffee in the beginning of oral life in patients operated on the lower gastrointestinal tract.: Importancia del uso del café en el inicio de la vida oral en pacientes operados de tubo digestivo bajo. - Montiel-Jarquín , Álvaro José (2024)
Background: The use of coffee in patients undergoing surgery of the lower gastrointestinal tract promotes the stimulation of peristalsis, favors tolerance to the initiation of the oral route as well as early progression to the soft diet. Objective: To present the clinical effects of starting the oral route with coffee in patients undergoing lower gastrointestinal tract surgery. Methods:  A descriptive study was performed to analyze the clinical effects of coffee in 14 postoperative patients of lower gastrointestinal tract surgery. The variables analyzed were: presentation of bowel sounds, expulsion of flatus, and effective evacuation.  Results: Fourteen patients were included, 9(64.3%) women and 5(35.7%) men, the use of coffee in patients with lower gastrointestinal tract surgery showed early progression to soft diet tolerance. Conclusions: The initiation of coffee in patients with lower gastrointestinal tract surgery improves motor activity in comparison to a traditional initiation to subsequently tolerate the soft diet.